Handbook of highly toxic materials handling and management - Grossel, Stanley S.; Crowl, Daniel A. (Environmental science and pollution control series, 1995)
"This unique single-source reference provides practical technological information on the toxicological aspects of dangerously hazardous chemicals, the design and maintenance of facilities for processing them, as well as preventive and mitigative procedures for controlling their accidental release." "Presenting the most comprehensive treatment of process safety and loss prevention relating to highly toxic materials - from both a design and an operating perspective - the Handbook of Highly Toxic Materials Handling and Management reviews key areas of industrial toxicology ... details the various components of an effective industrial hygiene program ... examines the equipment needed for personal protection ... highlights the plant design features and piping systems that are particularly important when handling highly toxic chemicals ... discusses the requirements for, and the various types of, pressure relief systems used in industry and methods for containing and disposing of their effluents ... delineates the essentials of good plant maintenance ... and more."--BOOK JACKET.